2018
DOI: 10.1182/blood-2018-99-120013
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Axicabtagene Ciloleucel CD19 CAR T-Cell Therapy in Elderly Patients with Relapsed or Refractory Large B-Cell Lymphoma

Abstract: Background Axicabtagene ciloleucel (axi-cel) is an autologous CD19-specific CAR T-cell therapy product that was FDA approved for the treatment of adult patients with relapsed or refractory large B-cell lymphoma after at least two lines of systemic therapy. In the pivotal ZUMA-1 study, the best overall response (ORR) and complete response (CR) rates observed in 108 patients treated with axi-cel were 82% and 58%, respectively. At a median follow-up of 15.4 months, 42% of the patients remain in ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This concern is also supported by the notion that comorbidities, the burden of which is typically higher in elderly patients than in younger patients, are associated with poor outcomes after axi-cel infusion (21). Two small, retrospective single-center studies that analyzed outcomes for patients 65 years or older (24 and 17 patients, respectively, in the two studies) and patients younger than 65 years (25 and 44 patients, respectively) who received axi-cel for relapsed or refractory large B-cell lymphoma showed comparable efficacies and rates of cytokine release syndrome (CRS) and neurotoxicity (22,23). Similar data were reported in a retrospective analysis of 177 Medicare patients (24).…”
Section: Special Scenarios: Patients With Aggressive B-cell Lymphoma mentioning
confidence: 99%
“…This concern is also supported by the notion that comorbidities, the burden of which is typically higher in elderly patients than in younger patients, are associated with poor outcomes after axi-cel infusion (21). Two small, retrospective single-center studies that analyzed outcomes for patients 65 years or older (24 and 17 patients, respectively, in the two studies) and patients younger than 65 years (25 and 44 patients, respectively) who received axi-cel for relapsed or refractory large B-cell lymphoma showed comparable efficacies and rates of cytokine release syndrome (CRS) and neurotoxicity (22,23). Similar data were reported in a retrospective analysis of 177 Medicare patients (24).…”
Section: Special Scenarios: Patients With Aggressive B-cell Lymphoma mentioning
confidence: 99%
“…[27] In terms of the relationship between age and the development of CRS the data are limited, but in a study of CAR T-cell therapy in patients with refractory large B-cell lymphoma there was not a significant difference in secondary effects between patients older and younger than 65 years. [28]…”
Section: Crs Risk Factorsmentioning
confidence: 99%
“…No treatment-related deaths were observed in a US multicenter cohort of 165 patients who received axicabtagenciloleucel for r/r DLBCL after commercialization outside of clinical trials [81]. Recently, safety of axicabtagenciloleucel was also confirmed in patients ≥65 years [83]. Further it has been reported that neurotoxicity is fully reversible in most patients [84].…”
Section: Chimeric Antigen Receptor T Cellsmentioning
confidence: 99%